Implementation Of Nafkah Iddah And Mut’ah In Divorce Cases In The Surabaya Religious Court - Arianty, Uzlifatus Dea Arianty; Abdullah Fikri (MIZAN: JOURNAL OF ISLAMIC LAW, 2025)
Divorce cases are still common in Indonesia, such as filing for divorce at the Surabaya Religious Court, which is recorded in thousands of cases each year, both divorces filed by the husband and contested divorces filed by the wife. When a divorce occurs between a husband and wife, the marital relationship between the two will break up, besides that, of course, there will be several rights and obligations that must be fulfilled by each party As a legal result of the divorce case, there will be an obligation to provide post-divorce maintenance for the ex-wife. This research was made to be able to analyze the implementation of post-divorce maintenance, which includes iddah maintenance and mut’ah maintenance for wives in the Surabaya Religious Court. The method used in this research is empirical juridical, and data collection is carried out by interviewing the Judge of the Surabaya Religious Court. The results of the study are needed to be able to see the implementation of the implementation of the provision of iddah alimony and mut’ah alimony to wives in the Surabaya Religious Court, which has differences in the implementation of the fulfillment of alimony from divorce and contested divorce, and often in the implementation process there are obstacles that can hinder the implementation process. The purpose of this research is also to be able to see the obstacles in the fulfillment of post-divorce maintenance in the Surabaya Religious Court, as well as the efforts made by the Surabaya Religious Court. Keywords: Divorce Cases, Iddah and Mut’ah Alimony, Wife’s Rights